1998
DOI: 10.1002/(sici)1096-9063(199806)53:2<165::aid-ps747>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Simple syntheses of malathion and malaoxon enantiomers, and isomalathion diastereoisomers: toxicity-configuration relationship

Abstract: Malathion enantiomers were synthesized by nucleophilic substitution of O,O-dimethyl dithiophosphoryl anion to diethyl (R)-or (S)-2-bromosuccinate. Malaoxon enantiomers were obtained from optically active malathions in thionoÈthiolo rearrangement with 65% Desmethylation of malathion HNO 3 . enantiomers by triethylamine, following the remethylation using methyl iodide gave isomalathion diastereomeric pairs. Physicochemical characteristics of the compounds obtained, and their inÑuence on rats and some species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Since the report that the R-enantiomer of MA showed preferential bioactivity over the corresponding S-enantiomer, the enantioselective toxicity of MA has received continual attention. Połećdetermined the enantioselective toxicity of the synthesized MA to the rats, housefly, cockroach, granary weevil, and two-spotted spider mite using standard toxicological methods 16 and observed that the R-configuration on the chiral found enantiomers with R-configuration showed higher toxicity to D. magna than S-forms and racemic forms. 17 Like most organophosphates, malathion is considered to be nonpersistent, and the degradation of rac-MA in soils, 18 in aquatic systems, 19 in terrestrial plants, and in animals has been widely reported.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the report that the R-enantiomer of MA showed preferential bioactivity over the corresponding S-enantiomer, the enantioselective toxicity of MA has received continual attention. Połećdetermined the enantioselective toxicity of the synthesized MA to the rats, housefly, cockroach, granary weevil, and two-spotted spider mite using standard toxicological methods 16 and observed that the R-configuration on the chiral found enantiomers with R-configuration showed higher toxicity to D. magna than S-forms and racemic forms. 17 Like most organophosphates, malathion is considered to be nonpersistent, and the degradation of rac-MA in soils, 18 in aquatic systems, 19 in terrestrial plants, and in animals has been widely reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since the report that the R -enantiomer of MA showed preferential bioactivity over the corresponding S -enantiomer, the enantioselective toxicity of MA has received continual attention. Połeć determined the enantioselective toxicity of the synthesized MA to the rats, housefly, cockroach, granary weevil, and two-spotted spider mite using standard toxicological methods and observed that the R -configuration on the chiral carbon atom caused the highest toxicity and the S -configuration the lowest toxicity. Recently, Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…Poiec investigated the enantioselective toxicity in rats, house-flies, cockroaches, granary weevils, and the twospotted spider mite; in all these bioassays, the R-configuration on the chiral carbon atom caused the highest toxicity, while the Sconfiguration caused the lowest toxicity [32]. Similarly, Hassan and Dauterman reported that the R-enantiomer of malathion shows preferential bioactivity over the corresponding S-enantiomers [33].…”
Section: Enantioselectivity In Acute Toxicitymentioning
confidence: 99%
“…Chiral enantiomers have the same chemical and physical properties in achiral environments, but they are often markedly different in terms of their biological activity such as, toxicity and environmental fate in chiral environments [1–3]. Organophosphorus pesticides (OP) are among the most important chemicals used for protection against agricultural and household pests.…”
Section: Introductionmentioning
confidence: 99%